Brand Equity Comparison:Make Over and Maybelline Cosmetics on TikTok App - Baiq Hilliyatil Auliya; Lukman Hakim (Universitas Lambung Mangkurat, 2025)
The era of globalization has transformed the business sector, presenting both opportunities and challenges for companies around the world. The impact of information and communication technology, especially the social media platform TikTok, has significantly changed the way companies interact with consumers. This study aims to compare the brand equity of two leading cosmetic brands in Indonesia, namely Make Over and Maybelline. Using a descriptive qualitative approach with a case study method, this research focuses on consumer interactions on TikTok, by analyzing four important elements of brand equity namely brand awareness, perceived quality, brand association, and brand loyalty. Data was collected from November 2 to December 2, 2024, using Brand24 for media monitoring. The results show that Maybelline leads in terms of brand awareness, perceived quality, and brand loyalty, while both brands show equally strong brand associations through their collaborations with international celebrities. However, Make Over showed a slight edge in terms of brand loyalty through higher video shares. This study provides valuable insights for companies looking to strengthen brand equity in the competitive digital market, as well as providing strategic recommendations for local and global brands in Indonesia.